Broadband, millimeter-wave antireflection coatings for cryogenic sintered aluminum oxide optics - Nadolski, Andrew Wade (2020)
"For more than fifty years, observations of the cosmic microwave background (CMB) have provided fundamental insights into the universe we inhabit. Through a combination of ground-based and balloon- and satellite-borne experiments, we have measured the CMB's temperature anisotropy and power spectrum to high precision (Barrow and Coles, 1991; de Bernardis et al., 2000; Planck Collaboration, 2016a). Most recently, experiments are attempting to measure the CMB's polarization anisotropy. Measurements of polarization anisotropy will provide insight into the epoch of reoinization, information about the energy scale of inflation, and characterization of galactic dust, for instance (Barkana and Loeb, 2001; Hu, 2003; Planck Collaboration, 2016b). These are difficult measurements to make, however. They require observations at both large and small angular scales, and sensitive instruments capable of observing at multiple wavelengths in order to constrain foreground contamination. One of the experiments contributing to this effort is the third generation survey camera on board the South Pole Telescope (SPT-3G; Benson et al., 2014}). SPT is located at the geographic South Pole (elevation ~2800 m), which is an exceptionally arid environment (Radford and Holdaway, 1998; Radford, 2011). A fifty year study of precipitable water vapor (PWV) at the South Pole found the average PWV is far less than 1 mm, making the South Pole one of the driest regions on Earth (Chamberlin and Grossman, 2012). This is important for telescopes observing at mm wavelengths, where atmospheric water vapor can severely attenuate the interesting radiation. Other perks of observing from the Pole are that the SPT can easily avoid the galactic plane and its dust-contaminated signal, enabling it to integrate on a patch of extragalactic sky for long periods. In addition, the low temperature variability of the six-month long polar night keeps the atmosphere stable for long stretches. The SPT optics and structure benefit from the low temperature variability as ...